The Presence of Picnic Space in Domestic Environment when COVID-19 Condition as Improving the Quality of Space and Mental Health - Hermin Werdiningsih; Indriatjario Soemadyo; Arnis Rochma Harani (Universitas Diponegoro, 2022)
The condition of the COVID-19 pandemic since 2020 has shaped changes in daily life, where the use of the living environment has become one of the things that have changed. Activities usually carried out outside the living environment now must be covered in it. In this paper, the domestic environment is understood as where private daily domestic activities usually occur. This paper aims to expand the understanding of picnic space in the domestic environment. Seeing how the picnic space is present in the domestic area has the potential to expand the understanding of space in architecture related to spatial quality. Investigates the relationship between activity and space as the basis for understanding the quality of space in a domestic environment. This paper uses a qualitative method to reveal the various activities and explores how the quality of space in the domestic environment has changed during the COVID-19 pandemic. Data was collected through direct observation, photos, interviews, and further analysis. The study finds that the domestic environment can appear as a picnic space with a relationship between humans and objects or an environment that supports happiness and improves mental health. The emergence of picnic space in the domestic environment occurs through three processes: the relationship between the supporting object, actor, and place, blurring the boundary of virtual and physical, and the relationship between object and atmosphere. The finding can enrich the field of architecture, especially in interpreting space, boundaries, and their relation to the mental health of its users.